1986
DOI: 10.1177/0008068319860302
|View full text |Cite
|
Sign up to set email alerts
|

On Some Asymptotic Results for Multivariate Autoregressive Models with Estimated Parameters

Abstract: In this paper the asymptotic equivalence of the estimated predictor and the optimal predictor of k-dimensional pth order autoregressive process in the stable case with dependent error variables bas been shown. An expression for the mean square error of the estimated predictor has also been derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…On the grounds of the results in Samaranayake and Hasza (1988) and Basu and Sen Roy (1986) (see also Lütkepohl, 1993, Sect. 3.5) we find that, for a Gaussian process…”
Section: Framework and Asymptotic Prediction Regionsmentioning
confidence: 93%
“…On the grounds of the results in Samaranayake and Hasza (1988) and Basu and Sen Roy (1986) (see also Lütkepohl, 1993, Sect. 3.5) we find that, for a Gaussian process…”
Section: Framework and Asymptotic Prediction Regionsmentioning
confidence: 93%
“…A preferable assumption would have been that estimation is based on the same sample that we intend to use for prediction, but exploiting only data up to the forecasting origin; Samaranayake and Hasza (1988) and Basu and Sen Roy (1986) have shown that many results obtained in the presence of the independence hypothesis remain valid under this more reasonable assumption. A preferable assumption would have been that estimation is based on the same sample that we intend to use for prediction, but exploiting only data up to the forecasting origin; Samaranayake and Hasza (1988) and Basu and Sen Roy (1986) have shown that many results obtained in the presence of the independence hypothesis remain valid under this more reasonable assumption.…”
Section: Forecasting With Estimated Linear Processes and Lütkepohl's mentioning
confidence: 99%
“…Most results obtained in this direction have to do with the combination of the estimation and the characteristic errors; we refer the reader to Baillie (1979), Reinsel (1980), Yamamoto (1980Yamamoto ( , 1981, Dufour (1985), Basu and Sen Roy (1986), Lütkepohl (1987), and Samaranayake and Hasza (1988). On the one hand, the stochastic nature of the time series models under consideration implies that the forecasts produced with them carry in their wake an error that cannot be minimized even if the parameters of the model are known with total precision; we refer to this as the characteristic error of the model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then since ε t 's and hence x t 's are continuous, n γ(0) is non-zero with probability one for sufficiently large n. Thus from Basu and Sen Roy (1986),…”
mentioning
confidence: 92%